2021
DOI: 10.1039/d1cs00380a
|View full text |Cite
|
Sign up to set email alerts
|

Green chemistry meets medicinal chemistry: a perspective on modern metal-free late-stage functionalization reactions

Abstract: This review summarizes the most recent advances of metal-free late-stage functionalization (LSF) of pharmaceutically relevant molecules. Particular emphasis is placed on C–H activation as well as the use of endogenous functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 178 publications
1
52
0
Order By: Relevance
“…In summary, we have successfully developed a robust synthetic methodology for α-(perfluoroalkylsulfonyl)propiophenones, envisioned as new members of photocleavable perfluoroalkylating reagents. In this work, we have demonstrated their scalability and applicability in the metal-, catalyst-and additive-free, redox-and pH-neutral perfluoroalkylation of electron-rich aromatics, as well as in the late-stage functionalization of small molecules such as caffeine, which is of great interest in the current literature [28]. In future work, we will explore the reach a Entries 1-12 were carried out with the perfluorohexyl analogue 1b, entries 13 and 14 with the perfluorooctyl analogue 1c; b using dimethylsulfone as a standard; c compact fluorescent lamp, 23 W. and applicability of these reagents for the functionalization of compounds of interest in academia and industry, namely, for the synthesis of molecules with novel properties in the fields of material and bioorganic chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we have successfully developed a robust synthetic methodology for α-(perfluoroalkylsulfonyl)propiophenones, envisioned as new members of photocleavable perfluoroalkylating reagents. In this work, we have demonstrated their scalability and applicability in the metal-, catalyst-and additive-free, redox-and pH-neutral perfluoroalkylation of electron-rich aromatics, as well as in the late-stage functionalization of small molecules such as caffeine, which is of great interest in the current literature [28]. In future work, we will explore the reach a Entries 1-12 were carried out with the perfluorohexyl analogue 1b, entries 13 and 14 with the perfluorooctyl analogue 1c; b using dimethylsulfone as a standard; c compact fluorescent lamp, 23 W. and applicability of these reagents for the functionalization of compounds of interest in academia and industry, namely, for the synthesis of molecules with novel properties in the fields of material and bioorganic chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the absence of metal catalysts, there is no metal residue in the product, reducing postprocessing costs, and avoids catalyst poisoning. 112 Considering this and in continuation of our efforts in green chemistry, we reported the first example to build functionalized polycyclic γ-lactams from 1,6-enynes through the dual α-C(sp 3 )-H oxidative functionalization of ketones in catalyst-and base-free systems (Scheme 60). 113 The proposed mechanism suggested that the α-carbonyl radical was formed by the oxidation of oxone.…”
Section: Radical Cyclization With Enyne Derivativesmentioning
confidence: 98%
“…Finally, the most beneficial directions of future research for substantial improvements for C–F bond functionalization are discussed. With a specific emphasis on the reaction designs, the substrate scopes, the underlying mechanisms, and their subsequent applications in the late-stage modification of complex molecules, 28 we hope that this timely and comprehensive review will bring relatively new vitality to medicinal and synthetic organic chemists who are interested in organofluorine chemistry and (hetero)cyclic chemistry.…”
Section: Introductionmentioning
confidence: 99%